Telaah atas Karya Tafsir di Indonesia: Studi atas Tafsir al-Bayan Karya Tm. Hasbi al-Siddiqi - Surahman Amin; Ferry Muhammadsyah Siregar (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2013)
This article discusses the characteristic of TM Hasbi as-Siddiqi’s Tafsir al-Bayan, its methodology and influence to the society. Indonesian Muslims’ reception toward this tafsir is also discussed. This article suggests that the the methodology of thre Quranic interpretation utilized in tafisr al-Bayan is analytical method or tahlili. This tafsir also puts emphasis on Islamic jurisprudence (fiqh), partly because the author of the Tafsir is reknowned as a professor in Islamic Law.